The Influence of Self-efficacy on Career Planning of Adolescents in High School - Firda Yuliani; Sry Ramadani; Putri Febriyanti Ramadhani; M. Murni; Putri Naila Artikasari; Ramli Ely (Golden Ratio of Data in Summary, 2026)
Career planning is a crucial indicator of life success, but many high school teenagers face obstacles, such as confusion and low self-understanding, when determining their future. This study aims to examine the influence of self-efficacy on career planning among high school students. The method used is library research with a qualitative approach, synthesizing scientific literature from the years 2015-2025, accessed through academic databases such as Google Scholar and ScienceDirect. The research findings indicate that self-efficacy has a positive and significant impact on career planning, as reported in various previous studies, with contributions ranging from 38.9% to 65.52%. Students with high self-efficacy demonstrate lower levels of career indecision and better job readiness, especially in the context of vocational education. Theoretically, these results reinforce the role of self-efficacy as the primary driver of exploring career options and setting challenging goals. The practical implications of this research emphasize that career guidance programs in schools should shift from merely providing job information to strengthening internal psychological factors through psychoeducational interventions and fostering a supportive learning culture. In conclusion, self-efficacy is a fundamental psychological foundation that enables students to plan and prepare themselves to face the workforce more maturely.